2014
DOI: 10.1186/2052-336x-12-79
|View full text |Cite
|
Sign up to set email alerts
|

Removal of tetracycline from wastewater using pumice stone: equilibrium, kinetic and thermodynamic studies

Abstract: In this study, pumice stone was used for the removal of tetracyline (TC) from aqueous solutions. It was characterized by XRD, FT-IR, SEM and BET analyses. Cation exchange capacity of pumice stone was found to be 9.9 meq/100 g. Effect of various parameters such as solution pH (2–11), adsorbent dosage (0.5-10 g/L), contact time (2.5-120 min), initial TC concentration (5–300 mg/L) and temperature (20–50°C) on TC adsorption onto pumice was investigated. Also the adsorption of TC on pumice stone was studied as a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 50 publications
5
48
1
Order By: Relevance
“…where q e and q t (mg/g) are the amounts of TC ions adsorbed on the adsorbent at equilibrium and time t (min), I is the intercept, and k 1 (min −1 ), k 2 (g/mg min), and k d (mg/g min 0.5 ) are the rate constants of pseudofirst-order kinetic model, pseudo-second-order kinetic model, and intraparticle diffusion model, respectively [45]. The values of correlation coefficients (k 1 , k 2 , k d ), equilibrium adsorption capacities (q e,teo ) in these models, and initial sorption rate (h) are given in Table 4.…”
Section: Kinetics Of Tc Adsorption Onto Adsorbentsmentioning
confidence: 99%
See 2 more Smart Citations
“…where q e and q t (mg/g) are the amounts of TC ions adsorbed on the adsorbent at equilibrium and time t (min), I is the intercept, and k 1 (min −1 ), k 2 (g/mg min), and k d (mg/g min 0.5 ) are the rate constants of pseudofirst-order kinetic model, pseudo-second-order kinetic model, and intraparticle diffusion model, respectively [45]. The values of correlation coefficients (k 1 , k 2 , k d ), equilibrium adsorption capacities (q e,teo ) in these models, and initial sorption rate (h) are given in Table 4.…”
Section: Kinetics Of Tc Adsorption Onto Adsorbentsmentioning
confidence: 99%
“…TC existed as cationic in strong acid solution at pH < 3.3, zwitter anions at 3.3 < pH < 7.7, and negative ions at pH > 7.7 [45]. Optimum experimental pH value was determined as 6 and TC molecules have negative and positive charge at this pH.…”
Section: Determination Of Ph Zpcmentioning
confidence: 99%
See 1 more Smart Citation
“…Since most antibiotics are poorly metabolized and absorbed by the treated humans and animals, large fractions are excreted through urine and feces as an unmodied parent compound. 3,4 The widespread use of antibiotics has caused a variety of potential adverse effects such as chronic toxicity, lowering of human immunity, 5 and dissemination into antibiotic-resistant genes. 6 Antibiotic pollution poses a potential threat to human health.…”
Section: Introductionmentioning
confidence: 99%
“…The results clearly indicate the strong adsorption affinity of red soil materials for TC. Bao et al (2008) 24) and Guler and Sarioglu (2014) 25) have also revealed the high adsorption ability of red soil and pumice stone for TC. In this flask experiments, TC removal by soil material was more rapid compared to microcosm-scale CW experiments (Table 2).…”
Section: Mechanisms Of Tc Removal By Cwsmentioning
confidence: 99%